2003
DOI: 10.1046/j.1365-8711.2003.06531.x
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter and visible baryons in M33

Abstract: In this paper we present new measurements of the gas kinematics in M33 using the CO J=1-0 line. The resulting rotational velocities complement previous 21-cm line data for a very accurate and extended rotation curve. The implied dark matter mass, within the total gaseous extent, is a factor 5 higher than the visible baryonic mass. Dark matter density profiles with an inner cusp as steep as R^{-1}, are compatible with M33 data. The dark matter concentrations required for fitting the M33 rotation curve are very … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
309
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(341 citation statements)
references
References 39 publications
30
309
1
1
Order By: Relevance
“…M 33 is in fact one of the very few objects for which it has been possible to combine a high quality and high resolution extended rotation curve (Corbelli & Salucci 2000) with a well determined distance (assumed in this paper to be D = 840 kpc, Freedman et al 1991;Gieren et al 2013), and with an overwhelming quantity of data across the electromagnetic spectrum. Previous analyses have shown that the HI and CO velocity fields are very regular and cannot be explained by Newtonian dynamic without including a massive dark matter halo (Corbelli 2003). On the other hand, the dark matter density distribution inside the halo is still debated because of the unconstrained value of the mass-to-light ratio of the stellar disk.…”
Section: Introductionmentioning
confidence: 99%
“…M 33 is in fact one of the very few objects for which it has been possible to combine a high quality and high resolution extended rotation curve (Corbelli & Salucci 2000) with a well determined distance (assumed in this paper to be D = 840 kpc, Freedman et al 1991;Gieren et al 2013), and with an overwhelming quantity of data across the electromagnetic spectrum. Previous analyses have shown that the HI and CO velocity fields are very regular and cannot be explained by Newtonian dynamic without including a massive dark matter halo (Corbelli 2003). On the other hand, the dark matter density distribution inside the halo is still debated because of the unconstrained value of the mass-to-light ratio of the stellar disk.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamical mass including a dark halo of the satellite galaxies, the LMC and M33 is still uncertain by a factor of 10 (e.g. Corbelli 2003;Seigar 2011;Kallivayalil et al 2013;van der Marel & Kallivayalil 2014). As indicated by Equation (6) and shown in Figure 4, the amplitude of the induced density is proportional to the satellite mass.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Corbelli (2003) found that dark halo mass out to 17 kpc from the center of M33 is ∼ 5 × halo surrounding M33 of (2.2 ± 0.1) × 10 11 M⊙ from the HI rotation curve. We assume that the mass and size of M33 are MM33 = 10 11 M⊙ and l = 17kpc, respectively.…”
Section: M31 -M33mentioning
confidence: 96%
“…The apparent stability of the M33 disk was raised by Padoan in his talk at this conference as a counterargument to the theory of gravitational instability, with a citation to Corbelli (2003). Examination of that paper shows that the star forming disk of M33 is indeed stable if only the gas is considered.…”
Section: Observational Comparisonsmentioning
confidence: 99%
“…Examination of that paper shows that the star forming disk of M33 is indeed stable if only the gas is considered. However, Corbelli (2003) also performed a simplified analysis including the stellar surface density, and concluded that the entire star-forming disk is indeed Toomre unstable if the stellar contribution is accounted for (see her Fig. 8).…”
Section: Observational Comparisonsmentioning
confidence: 99%